PENGUJIAN KANDUNGAN INFORMASI PADA PENGUMUMAN PEMECAHAN SAHAM DI INDONESIA - Adnyani, Ketut Sonya; Putri, IGAM Asri Dwija (E-Jurnal Akuntansi, 2015)
This research aims to find out an empirical evidence about the market reaction of stock split as measured by the difference of abnormal return on companies that listed in Indonesian Stock Exchange. There were 38 companies that has done the stock split. Secondary data were used for this research with sampel selection using a purposive sampling method. Technical analysis used for different test is wilcoxon signed ranks test at level of significant five percent. This is an 11-day observation period. That data normality was tested by kolmogorov smirnov. The results of this study showed that were no significant differences of abnormal return before and after stock split.
Keywords: stock split, abnormal return, market reaction